أثر القراءات القرآنية في الدلالة الصوتية (Athar al-Qiraat al-Quraniyah fi al-dilalat al-sawtiyah) - Abdul Majid, Abu Saiid Muhammad; Chik, Abdul Rahman (IIUM Press, 2009)
Qiraat al-Quran and semantics